High performance Cu/Cu2O nanohybrid electrocatalyst for nonenzymatic glucose detection. Issue 27 (21st June 2016) - Cheng, Xiqing; Zhang, Jun; Chang, Hucheng; Luo, Liqiang; Nie, Fuqiang; Feng, Xinjian
Abstract : Described herein are Cu/Cu2 O nanohybrids prepared via potential oscillation, and their high performance for nonenzymatic glucose detection applications. Abstract : Here we report Cu/Cu2 O nanocomposites prepared via potential oscillation. High resolution transmission electron microscopy images reveal a homogeneous distribution of Cu and Cu2 O in the composite. Due to the synergistic effect between Cu and Cu2 O, the nanohybrids show much lower resistivity and higher glucose oxidation activity (a lower over-potential and higher current-output) compared to the Cu2 O counterpart. As an example of application, a nanocomposite-based electrode is employed for a nonenzymatic glucose biosensor application, and exhibits a linear detection upper limit of 40 mM, a sensitivity of 1434.12 μA cm −2 mM −1, and good selectivity.